Mean streets : migration, xenophobia and informality in South Africa - Crush, Jonathan, 1953-; Chikanda, Abel; Skinner, Caroline ([Cape Town] : The Southern African Migration Programme (SAMP) : The African Centre for Cities : The International Development Research Centre, 2015)
"This book powerfully demonstrates that some of the most resourceful entrepreneurs in the South African informal economy are migrants and refugees. Yet far from being lauded, they take their life into their hands when they trade on South Africa's 'mean streets'. The book draws attention to what they bring to their adopted country through research into previously unexamined areas of migrant entrepreneurship. Ranging from studies of how migrants have created agglomeration economies in Jeppe and Ivory Park in Johannesburg, to guanxi networks of Chinese entrepreneurs, to competition and cooperation among Somali shop owners, to cross-border informal traders, to the informal transport operators between South Africa and Zimbabwe, the chapters in this book reveal the positive economic contributions of migrants. these include generating employment, paying rents, providing cheaper goods to poor consumers, and supporting formal sector wholesalers and retailers. As well, Mean Streets highlights the xenophobic responses to migrant and refugee entrepreneurs and the challenges they face in running a successful business on the street"--Provided by publisher
Chapter 1. Migrant Entrepreneurship and Informality in South African Cities / Jonathan Crush, Abel Chikanda and Caroline Skinner -- Chapter 2. Doing Business with Xenophobia / Jonathan Crush and Sujata Ramachandran -- Chapter 3. Making an Area Hot : Interrupting Trade in an Ethnic Enclave in Johannesburg's Inner City / Tanya Zack -- Chapter 4. A Transnational Space of Business : The Informal Economy of Ivory Park, Johannesburg / Andrew Charman and Leif Petersen -- Chapter 5. Resilience and Innovation : Migrant Spaza Shop Entrepreneurs in Soweto, Johannesburg / Trynos Gumbo -- Chapter 6. The Role of Economic Factors and Guanxi Networks in the Success of Chinese Shops in Johannesburg / Lodene Willemse -- Chapter 7. On the Move : Cameroonian Migrants in Durban / Akwa Tafuh and Pranitha Maharaj -- Chapter 8. Refugees and Asylum Seekers in Cape Town's Informal Economy / Madeleine Northcote and Belinda Dodson -- Chapter 9. The Role of Migrant Traders in Local Economies : A Case Study of Somali Spaza Shops in Cape Town / Vanya Gastrow and Roni Amit -- Chapter 10. The Role of Networks and Herd Behaviour in the Entrepreneurial Activity and Success of African Migrants in South Africa / Robertson K. Tengeh -- Chapter 11. The Malayisha Industry and the Transnational Movement of Remittances to Zimbabwe / Vusilizwe Thebe -- Chapter 12. Transnational Entrepreneurship and Informal Cross-Border Trade with South Africa / Sally Peberdy, Jonathan Crush, Daniel Tevera, Eugene Campbell, Nomsa Zindela, Ines Raimundo, Thuso Green, Abel Chikanda and Godfrey Tawodzera -- Chapter 13. Unpacking National Policy Towards the Urban Informal Economy / Christian M. Rogerson.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Immigrants -- South Africa -- Economic conditions; Xenophobia -- South Africa; Street vendors -- South Africa; Peddlers -- South Africa; Informal sector (Economics) -- South Africa; Entrepreneurship -- South Africa; Xénophobie -- Afrique du Sud; Vendeurs de rue -- Afrique du Sud; Colporteurs -- Afrique du Sud; Secteur informel (Économie politique) -- Afrique du Sud; Entrepreneuriat -- Afrique du Sud; "Museum, historic sites, gallery & art guides."; SOCIAL SCIENCE -- Emigration & Immigration; Entrepreneurship; Immigrants -- Economic conditions; Informal sector (Economics); Peddlers; Street vendors; Xenophobia; South Africa